Limb salvage in epithelioid sarcoma like hemangioendothelioma invading femur mid shaft: a case report - S. Chinder, Pramod; Samorekar, Bheemsingh; Krishnamoorthy, Naveen; B.T., Rangaswamy (International Journal of Medical Research and Review, 2015)
Epithelioid sarcoma like hemangioendothelioma (ES-H) is recently added vascular soft tissue tumor in WHO list, with high propensity for infiltrative growth, local recurrence and low metastatic potential. We present a twenty year old male with right mid thigh swelling with pain since five months whose x-rays showed osteolytic, scalloped lesions of mid shaft femur. On workup was diagnosed ES-H for which wide excision of tumor was done and limb salvaged with biological reconstruction using free vascularised fibula.